Analisis Kebutuhan Sarana dan Prasarana untuk Mendukung Proses Pembelajaran di SMK Negeri 1 Surabaya - Ananda, Ardhea Dwi; Rofidah, Arini Nur; Devanatasha, Shelma; Ahsyabila, Chantika Putri; Wulandari, Ayu (TSAQOFAH, 2025)
Vocational education, secondary school facilities and infrastructure play animportant role in the learning process. Management of facilities and infrastructure needs to be done well to achieve success and support the teaching and learning process in vocational schools. To achieve success, the learning process must be supported by the availability of adequate facilities and infrastructure as well as optimal managemet by referring to the management of facilities and infrastructure. This research aims to analyze the need for facilities and infrastructure to supportan optimal learning process at SMK Negeri 1 Surabaya. This article was written using qualitative approach. Through data collection through interviews, documentation, and supported by direct observation at SMK Negeri 1 Surabaya with an approach to he students. It can be concluded that the results of this research show that the dominant facilities and infrastructure at SMK Negeri 1 Surabaya have been utilized optimally. Things to support practice in vocational schools, such as computer labs, as well as studios and other equipment that supports the learning process, are said to be very adequate. Maintenance of facilities and infrastructure has also been carried out periodically. The available facilities and infrastructure greatly increase student enthusiasm for learning and achievement.onclusions.